Prevention Effectiveness of Non-Performing Financing in the Indonesian Islamic Bank - M. Mutawali; Ahmad Rodoni; Muhammad bin Said (ETIKONOMI, 2019)
Islamic banking still has a high ratio of non-performing financing. This study analyzes the causes of non-performing financing, along with the prevention effectiveness and resolution strategies performed by Islamic banks in dealing with this problem. Interviews conducted on nine informants, with questionnaires distributed to 30 respondents. The results show that the prevention effectiveness performed by Islamic banks consists of legal aspects, qualified human resources, and criteria assessment used to finance proposals, and improve risk management. Furthermore, internal factors such as default, information asymmetry, and financial stress were attributes of non-performing financing, which is externally influenced by inflation, GDP decline, natural disasters, interest rates, and political criminality.JEL Classification: G21, G32